Advances in bistatic radar - Willis, Nicholas J. 1934-; Griffiths, H. 1956- (Hugh) (SciTech Publishing, 2007)
This comprehensive reference updates bistatic and multistatic radar developments since the publication of Nicholas Willis' seminal book Bistatic Radar published in 1991 and revised in 1995. The book is organized into two major sections: Bistatic/ Multistatic Radar Systems and Bistatic Clutter and Signal Processing. New and recently declassified military applications are documented. Civil applications are detailed for the first time, including commercial and scientific systems. Several of the most honored radar engineers of this era provide expertise in each of these applications. Professionals in radar and sonar will find this book a valuable resource.